Սոկրատ Սքոլաստիկոսի «Եկեղեցական պատմության» ու Սիղբեստրոսի վարքի հայերեն համառոտման և հարակից հարցերի շուրջ - Մուշեղյան, Ալբերտ («Նաիրի» հրատ.)
В армянской традиции существует несколько совместных копий сокращенных редакций “Жития Сильвестра” и “Церковной истории” Сократа Схоластика (“Малый Сократ”, более поздние авторы применяли это заглавие к совместному тексту двух трудов, т.к. он начинается с предисловия, приписанного Сократу). Редактирование в 696 г. осуществил Филон Тиракаци по приказу католикоса Саака Дзорапореци, дополнив эпизодами из армянской истории, а также антихалкидонскими выпадами. “Большой Сократ” – это собственно перевод “Церковной истории”, т.е. несколько сокращенный вариант греческого оригинала (Филон Тиракаци опустил некоторые детали: письма, речи и т.п.). Житие римского епископа Сильвестра по всей вероятности было переведено в 40-х гг. V века. Краткие армянские редакции “Церковной истории” Сократа Схоластика и “Жития Сильвестра” с 90-ых годов XIX века применялись гиперкритиками для доказательства, якобы отец армянской историографии Мовсес Хоренаци пользовался ими и, следовательно, жил не в V, а в VIII-IX вв. Статья посвящена разбору соотношений вышеуказанных произведений. In the Armenian tradition there exist several joint copies of the shorter recensions of the Life of Silvester and Socrates Scholasticus‟ Ecclesiastical History (Shorter Socrates, later authors used this title for the joint texts of both writings, since it starts with an introduction ascribed to Socrates). The texts were revised in 696 by P„ilon Tirakac„i by the order of catholicos Sahak Dzorap„orec„i, who added episodes from the Armenian history and anti-Chalcedonian attacks. Longer Socrates is the Armenian version of the Ecclesiastical History proper, i.e. the slightly abridged variant of the Greek original (P„ilon Tirakac„i omitted some details: letters, sermons etc.). The Life of Silvester was probably translated in the 40-ies of the V c. Starting with the 90-ies of the XIX c., the shorter recentions of Socrates Scholasticus‟ Ecclesiastical History and the Life of Silvester, bishop of Rome, were used by hypercriticists as an alleged proof that Father of Armenian historiography Моvsēs Хоrenac„i made use of them, consequently, he lived not in the V, but in the VIII-IX cc. The article deals with the analysis of the relations of the above-mentioned texts.
Keywords: Բանասիրություն